Three-dimensional digital reconstruction of human placental villus architecture in normal and complicated pregnancies. (February 2016) - McCarthy, R.; Orsi, N.M.; Treanor, D.; Moran, O.; Vernooij, M.; Magee, D.R.; Roberts, N.; Stahlschmidt, J.; Simpson, N.A.B.
Abstract: Objective: This study aimed to examine the use of digital technology in the three-dimensional reconstruction of human placentas. Study design: Placentas obtained at term elective caesarean section were sampled, formalin-fixed and embedded in paraffin. Two hundred 5 μm consecutive sections were cut from each specimen and the resultant slides stained with haematoxylin and eosin. Slides were then scanned and the digitised images reconstructed using customised software. Results: Three-dimensional reconstructions were successfully achieved in placentas from normal pregnancies and those complicated by pre-eclampsia, growth restriction, and gestational diabetes. Marked morphological differences were readily identifiable, most clearly in the stem villus architecture. Conclusion: This method is an emerging research tool for examining placental histoarchitecture at high resolution and gaining clinically relevant insight into the placental pathology allied to pregnancy complications such as PET, IUGR and GD.